Análise de corrosão por meio de perda de massa e espessura em aços pela ação da água produzida de poços petrolíferos - Souza, Erivaldo Dias de (2010)
This work was carried out aiming the study of the corrosion effect by the water produced, which is associate to the production of oil, mainly in wells in mature fields, such as the UN-SEAL. It is noteworthy that this water is known in the petroleum industry as water produced. The sample of produced water used was of the production field of Siririzinho I on-shore in Sergipe, which showed in its physicalchemical analysis, high levels of salinity among other compounds, which makes it an extremely aggressive corrosion for materials used in the petroleum industry. In this research the materials used in this work were the carbon steel ASTM A283 Gr C, the stainless steel ASTM A240 type 316L with and without coating of hard chrome and the duplex stainless steel ASTM A890 Gr 1B. The sample used had chemical compositions issued by manufacturers according to ASTM, in addition, microhardness tests and metallographic tests with the use of optical microscopy were used to characterize these materials. For the study of effect of the water produced attack in the materials, was designed and built a test circuit, which allowed the insertion of samples for monitoring and data collected of mass and thickness parameters , and the monitoring visual corrosion during the test. The samples were machined in two geometric shapes (rectangular plate and disk) to enable and facilitate the testing of weight and thickness measurement by applying the ultrasound technique and of the depth measurement. From the collected data was possible to calculate by established criteria using the standard NACE RP 0775, the rate of uniform corrosion by mass loss and by its development the rate of corrosion by thickness loss, that is the same form used for the calculation of corrosion rate by pit in agreement with the standard Petrobras N- 2364. By comparing the corrosion rates obtained in the study, can better evaluate the possible perspectives of application of the materials in contact with the corrosive fluid.